Effect of sandalwood essential oil aromatherapy (Santalum Album L) on the intensity of labor pain reduction in the first stage at Elliani Silau Laut Clinic in 2023 - Ririn Anggriani Sitorus; Selvi Puspan Sari; Debby Pratiwi (Institute of Computer Science (IOCS), 2023)
The traditional plant sandalwood is an essential oil producer because of its distinctive terrace wood properties and contains oil with a specific aroma. Essential oils contained in sandalwood are a class of sesquiterpenoid compounds including a-santalol and b-santalol. Sandalwood oil has functions including as an aromatherapy material that is very beneficial for human health. This type of research using the Quasy Experiment method with Case Control pretest postest design, In this study the samples taken were 30 women in labor during the first stage. The sampling technique used total sampling. Statistical test results using the t-test paired sample test. Data analysis obtained is the intensity of labor pain during the first stage before giving sandalwood essential oil aromatherapy the majority experienced severe pain intensity as many as 16 respondents (53.3%) and 14 respondents (46.7%) in the moderate category. While the intensity of labor pain in the first stage after the administration of sandalwood essential oil aromatherapy, the majority experienced mild pain intensity as many as 18 respondents (60.0%), 10 respondents (33.3%) in the moderate category and 2 respondents (6.7%) in the severe category. The results of the analysis showed that the administration of sandalwood essential oil aromatherapy proved effective in reducing the intensity of labor pain during the first stage of labor.)